Management Strategies for On-street Parking Facility at Gen. Sudirman Street Kuanino Kupang - Pedo, Krisantus Satrio Wibowo; Pattiraja , Agustinus Haryanto (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
Poor performance of on-street parking facilities at Gen. Sudirman Kuanino Street, Kupang, can disrupt traffic flow and cause various problems. The research method is to evaluate the performance of on-street parking facilities and their impact on road performance, transportation costs, and the environment. The results show that the parking index exceeds the parking space capacity, with the highest values of 150% (left) and 138% (right). This is due to the parking volume of building material store operational vehicles (pick-ups and trucks). The resulting impact is a decrease in road performance with a degree of saturation (DS) at 1.22. Hence, it affects transportation costs and vehicle exhaust emissions exceeding regulatory limits. The recommended structuring strategy is the application of rules to control the volume, space, and time of parking by prohibiting parking from building material store operational vehicles, requiring minimum availability of off-street parking spaces by every store, applying a progressive parking fee system, and planting green plants. If the structuring strategy is implemented, the highest parking index results are 84% (left) and 96% (right), and the road performance results increase from the DS value of 1.22 to 0.71.